ADSORPSI SENYAWA ASAM BENZOAT MENGGUNAKAN KARBON AKTIF BATANG PISANG (Musa Paradisiaca. L) - Iswara, Muhammad Wahyugo; Sitorus, Saibun; Gunawan, Rahmat (JURNAL ATOMIK, 2022)
Research on the adsorption of benzoic acid compounds using activated carbon of banana stems (Musa paradisiaca L) has been carried out. The method used is adsorption with activated adsorbent modification. SEM morphological results on banana stems showed differences before and after activation. From the research results obtained the optimum adsorption concentration of activated carbon of banana stems at adsorbent weight of 0.6 grams, xylene concentration of 40 ppm and adsorption capacity of 1.165 mg/g. Optimum time of activated carbon of banana stem was 0.4 gram, adsorption time was 45 minutes and adsorption capacity was 1.772 mg/g.